Core set of unfavorable events of shoulder arthroplasty: an international Delphi consensus process - Audigé L., Schwyzer H.; Shoulder Arthroplasty Core Event Set (SA CES) Consensus Panel; Durchholz H (Mosby Inc., 2022)
Background
Shoulder arthroplasty (SA) complications require standardization of definitions and are not limited to events leading to revision operations. We aimed to define an international consensus core set of clinically relevant unfavorable events of SA to be documented in clinical routine practice and studies.
Methods
A Delphi exercise was implemented with an international panel of experienced shoulder surgeons selected by nomination through professional societies. On the basis of a systematic review of terms and definitions and previous experience in establishing an arthroscopic rotator cuff repair core set, an organized list of SA events was developed and reviewed by panel members. After each survey, all comments and suggestions were considered to revise the proposed core set including local event groups, along with definitions, specifications, and timing of occurrence. Consensus was reached with at least two-thirds agreement.
Results
Two online surveys were required to reach consensus within a panel involving 96 surgeons. Between 88% and 100% agreement was achieved separately for local event groups including 3 intraoperative (device, osteochondral, and soft tissue) and 9 postoperative event groups. Experts agreed on a documentation period that ranged from 3 to 24 months after SA for 4 event groups (peripheral neurologic, vascular, surgical-site infection, and superficial soft tissue) and that was lifelong until implant revision for other groups (device, osteochondral, shoulder instability, pain, late hematogenous infection, and deep soft tissue).
Conclusion
A structured core set of local unfavorable events of SA was developed by international consensus to support the standardization of SA safety reporting. Clinical application and scientific evaluation are needed.